2017
DOI: 10.1111/wrr.12540
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mycobacterium marinum infections in zebrafish wounds and sinus tracts

Abstract: The impaired healing of Mycobacterium tuberculosis-infected wounds is a clinical challenge, and the mechanisms involved are still not clear. The zebrafish model of Mycobacterium marinum infection has provided surprising insights into the pathogenesis of tuberculosis in humans. Similarly, the major principles and phases of cutaneous wound healing are conserved among adult mammals and adult zebrafish. Here, we injected Mycobacterium marinum into the dorsal muscles of adult zebrafish and observed the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…37 Our high-throughput RNA sequencing showed that the expressions of IL-1β and TNF-α were upregulated in zebrafish tuberculous wound samples. 38 Because both IL-1β and TNF-α promote FM formation by an autocrine function 39 or by activating the NF-κB pathway, 40 we speculated that FM may play a role as a unique pro-inflammatory macrophage during tuberculous wound pathogenesis. The specific distribution of FM in different types of wound tissues may indicate the reasons for the difficulty of tuberculous wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…37 Our high-throughput RNA sequencing showed that the expressions of IL-1β and TNF-α were upregulated in zebrafish tuberculous wound samples. 38 Because both IL-1β and TNF-α promote FM formation by an autocrine function 39 or by activating the NF-κB pathway, 40 we speculated that FM may play a role as a unique pro-inflammatory macrophage during tuberculous wound pathogenesis. The specific distribution of FM in different types of wound tissues may indicate the reasons for the difficulty of tuberculous wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…ESAT-6 and CFP-10 are RD1 (region of difference) that induce IFN-gamma production infected with MTB and pathogenic Mycobacterium bovis [11]. Mycobacterium marinum is closely related to MTB in terms of genomic analysis, which could be the reason behind the cross-reactivity to the tuberculin skin test [12].…”
Section: Discussionmentioning
confidence: 99%
“…24 The mean time of the formation of a tuberculous wound in zebrafish induced by Mycobacterium marinum was 59 days. 21 In contrast, local swelling was still found at 15-days after injection in rat models of tuberculous wound induced by BCG (1 × 10 6 CFU). 15 In this study, local abscess with positive results in acid-fast staining were found in rat models, which confirmed that rat models of tuberculous wound were successfully induced.…”
Section: Animal Models Of Tuberculous Woundmentioning
confidence: 96%
“…Animal models could offer a good platform for various scientific research activities. Previous studies 17 have reported the successful induction of models in various animals, such as the rabbit, 18,19 mouse, 20 rat, 15 zebrafish, 21 and monkey. 22 Our team has already successfully induced rat models of a tuberculous wound by using viable BCG (1 × 10 7 CFU/ site).…”
Section: Animal Models Of Tuberculous Woundmentioning
confidence: 99%